Does Experience Guide People to Rebuy? Brand Loyalty at Ice Cream Shops in Yogyakarta - Kurniadita, Yuan Adelintang (Hasanuddin Economics and Business Review, 2024)
Food tourism is a major attraction for tourists because it provides an unforgettable experience. Yogyakarta is a tourist destination that is increasingly in demand because of its contemporary culinary concept. This research aims to determine the phenomenon of the experience of visitors to ice cream shops in Yogyakarta in enjoying ice cream in a shop with a unique concept in a tropical atmosphere. The brand experience felt by the ice cream shop customers was tested for its influence on brand loyalty. The concept of brand trust is also tested as a mediator of the relationship between brand experience and brand loyalty based on the commitment-trust theory. The formation of brand loyalty through the concepts of experience and trust is closely related to long-term brand-customer relationship management. A total of 179 data were analyzed using the PLS-SEM method. The research results show that brand experience has a positive significant effect on brand loyalty. In an indirect relationship, brand trust partially mediates the relationship between brand experience and brand loyalty.